Integrating Islamic Values in the Theory and Practice of Entrepreneurship. An Analysis in Higher Learning Institution in Malaysia - Rashidi, Abbas; Fakhrul Adabi, Abdul Kadir; Ilhamie, Abdul Ghani Azmi (Contemporary Research Center, Australia, 2013)
This study was conducted to determine the correlation between element of soft skills and Islamic values among students in Higher Education in Malaysia. The sample groups are undergraduate students of Malaysian Technical University Network (MTUN) - Universiti Malaysia Pahang (UMP), Universiti Teknikal Malaysia Melaka (UTeM), Universiti Tun Hussein Onn (UTHM) and Universiti Malaysia Perlis (UNiMAP). The number of respondents is 480 people and distributed to the respondents using cluster sampling techniques and simple random sampling. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 19.0 for the mean, standard deviation and Pearson correlation. The findings showed the significant and weak of correlation between integrity and entrepreneurship skills. Meanwhile, there is significant and moderate correlation between sincerity, trustfulness with entrepreneurship skills. However, data shows high ability in terms of mastery of soft skills such as entrepreneurship skills, integrity, sincerity and trustfulness. Lastly, proper attention should be given to this realm in order to further enhance the students' potential as well as to improve the performance of university.